Sustaining nature, transforming society: rethinking sustainability through radical ecopolitical thought - Means, Morgann K. R., author; MacDonald, Bradley, advisor; Stevis, Dimitris, committee member; Trembath, Paul, committee member (Colorado State University. Libraries, 2013)
Sustainability represents a central idea in environmental political thought that provides a conceptual framework for constructing, discussing, and judging the viability of solutions for ecological degradation. Despite the recent predilection for perceiving sustainability as a powerful discursive construct capable of capturing the pursuit of economic prosperity, societal well-being, and ecological vitality within a unified political project, the definition of the notion remains ambiguous and contested throughout the literature. This ambiguity has resulted in concern over the viability of the sustainability concept to induce beneficial transformation and has led to suggestions that the notion is rapidly losing its meaning as a coherent program for environmentally and socially positive change. In response to the ambiguity present in discussions of sustainability and the resulting concern over the diminishing meaning and significance of the term, this thesis constructs a typological analysis of sustainability. It divides the concept into three analytic categories—sustainability as a goal, as a human right, and as a need—in order to critically evaluate the multi-faceted articulations of the term within reformist environmental discourse. Identifying the common objectives of the typological categories, as well as the clear differences between the three reformist discourses regarding the impetus behind sustainability and the agents and processes involved in the transition to a sustainable condition, this thesis critically challenges reformist conceptualizations of sustainability. It then explores three radical ecopolitical discourses—ecocentrism, social ecology, and ecofeminism—in order to examine their potential to re-imagine sustainability and establish coherent conceptual boundaries for its realization. The final chapter of this thesis evaluates the feasibility of the radical ecopolitical paradigms by discussing potential openings for each position to enter into the existing conversation regarding human-nature interactions and to fundamentally restructure the objectives of sustainability, as well as the agents and processes involved in its pursuit.
Keywords: ecocentrism; ecofeminism; ecopolitics; environmental theory; social ecology; sustainability